The impact of board structure on financial leverage of Vietnamese listed firms - Hoàng, Mai Phương (2022)
This study examines the impact of board structure on financial leverage decisions, as measured by the ratio of total debt to total assets, of nonfinancial firms listed on the Ho Chi Minh City Stock Exchange. Based on a dataset of 1,592 observations collected from 199 firms for the period from 2012 to 2019, the analysis shows a correlation between board characteristics and a firm’s financial leverage. Specifically, the higher the number of annual board meetings or the larger the number of female members on the board of directors, the lower the rate of financial leverage. On the other hand, the size of the board and the presence of CEOs on the board do not have a significant influence on financial leverage decisions. A robust test using the system of generalized method of moments (GMM) to control for endogeneity generally confirms the results.